Eculizumab Dosing Regimen in Atypical HUS: Possibilities for Individualized Treatment. Issue 4 (26th May 2017) - Volokhina, E; Wijnsma, K; van der Molen, R; Roeleveld, N; van der Velden, T; Goertz, J; Sweep, F; Brüggemann, RJ; Wetzels, J; van de Kar, N; van den Heuvel, L
Abstract : Recent studies indicate that eculizumab is often given in excess to atypical hemolytic uremic syndrome (aHUS) patients. Individualization of treatment is thus highly requested; however, data on the pharmacokinetics and pharmacodynamics of eculizumab remain limited. We analyzed 11 patients during induction (weekly), maintenance (2‐weekly), and tapering (every 3–8 weeks) phases of treatment. The trough eculizumab levels increased with each additional dose during the induction phase (depending on body weight). During maintenance, high eculizumab concentrations of up to 772 μg/mL were observed. The levels decreased with each following dose during tapering (3‐ and 4‐week intervals); however, three patients maintained target eculizumab levels over long time periods (30–48 weeks). At intervals of 6–8 weeks, target eculizumab levels were no longer attained. Serum samples with eculizumab concentrations ≥50 μg/mL showed adequate complement blockade. Our data provide essential insight for optimization of eculizumab dosing schemes and lessening of therapy burden for the patients and cost of the treatment.